2003
DOI: 10.1089/104303403322542310
|View full text |Cite
|
Sign up to set email alerts
|

Protective Immunity Evoked Against Anthrax Lethal Toxin After a Single Intramuscular Administration of an Adenovirus-Based Vaccine Encoding Humanized Protective Antigen

Abstract: Because of the need to develop a vaccine to rapidly protect the civilian population in response to a bioterrorism attack with Bacillus anthracis, we designed AdsechPA, a replication-deficient human serotype 5 adenovirus encoding B. anthracis protective antigen (PA) with codons optimized for expression in mammalian cells. With a single intramuscular administration to mice of 10(9) particle units of AdsechPA, a dose that can be scaled to human use, anti-PA antibodies were evoked more rapidly and at a higher leve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 62 publications
2
43
0
1
Order By: Relevance
“…Adenovirus-vectored recombinant vaccines expressing a wide array of antigens have been constructed and protective immunity against different pathogens has been demonstrated in animal models [21][22][23][24][25]. In our research, we demonstrated the efficacy of using an adenovirus-based vaccine for single-time genetic vaccination that provided long-lasting protective immunity against botulism caused by botulinum neurotoxin type C.…”
Section: Introductionmentioning
confidence: 72%
“…Adenovirus-vectored recombinant vaccines expressing a wide array of antigens have been constructed and protective immunity against different pathogens has been demonstrated in animal models [21][22][23][24][25]. In our research, we demonstrated the efficacy of using an adenovirus-based vaccine for single-time genetic vaccination that provided long-lasting protective immunity against botulism caused by botulinum neurotoxin type C.…”
Section: Introductionmentioning
confidence: 72%
“…Tan et al (30) first developed an adenovirus-based vaccine encoding humanized PA and evaluated the efficiency of this vaccine in a mouse model; the LT challenge showed that 72% of the mice survived 27 days after vaccination and 27% survived on day 11. Next, a nonhuman primate adenovirus, AdC7, was used as the vaccine vector in order to overcome the preexisting neutralizing antibodies against Ad5 in humans (31).…”
Section: Discussionmentioning
confidence: 99%
“…AdsechPA afforded approximately 2.7-fold more protection than the rPA vaccine against B. anthracis lethal toxin challenge four weeks after a single intramuscular administration, suggesting the potential of this vaccine to protect the civilian population against B. anthracis in response to a bioterrorism attack (Tan et al, 2003). Chimeric virus-like particles (VLPs), which are very effective at eliciting humoral as well as cellular immunity, were also tested.…”
Section: Dna Vaccinesmentioning
confidence: 99%